Pengaruh Bokashi Eceng Gondok Terhadap Pertumbuhan Cabai Rawit (Capsicum frutescens L.) Varietas Hiyung Pada Fase Vegetatif - Muhammad Ahyan; Antar Sofyan; Akhmad Gazali (Universitas Lambung Mangkurat, 2019)
Cayenne pepper (Capsicum frutescens L.) the one is horticultural plants of the Solanaceae family that has high economic value. Cayenne pepper is used as a spice in cooking and medicine. The average national production of cayenne pepper in 2009 was 5.89 t ha-1, whereas in South Kalimantan in 2009 it was 4.4 t ha-1. This was due to uncertain season, also the handling of how to cultivate cayenne cultivation was less than the maximum For example, irrigation is still a matter of relying on rain and the use of seeds that are not selected, as well as the application of fertilizers that are not optimal. Water hyacinth is an alternative source of organic material that is widely available in waters that are not utilized, but can be used as pupu bokashi. This study aims to determine the different effects of the administration of several types of bokashi fertilizer to the growth of the chili variety in the vegetative phase. This study uses a completely randomized one factor in the form of water hyacinth dose consisting of 5 levels, P0 = Control (5 kg soil + 1 kg chicken manure fertilizer) / poly bag P1 = 10% g bokashi water hyacinth P2 = 20% g bokashi fertilizer water hyacinth P3 = 40% g bokashi fertilizer water hyacinth P4 = 80% g bokashi fertilizer water hyacinth. The observation variables in this study were plant height, stem diameter and number of flowers. The results of this study show that the application of water hyacinth bokashi has a significant effect on the diameter of the stem at the age of 35 HST where the best treatment is in the treatment P4 = 80% g of bokash ieceng goiter with 0.60 cm in diameter.